Arabic Learning Media Based on Smart Apps Creator for Students of Islamic Junior High School - Umi Hijriyah; Koderi Koderi; Erlina Erlina; Irwandani Irwandani; Muhammad Aridan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aimed to develop, know the feasibility, know the response, and analyze the effectiveness of Arabic learning media based on smart apps creator for class VIII MTs students. This development research uses the Dick and Carey development model, with ten stages, namely identifying learning objectives, conducting instructional analysis, analyzing student characteristics and learning contexts, formulating specific learning objectives, developing assessment tools or instruments, developing learning strategies, developing and selecting teaching materials, designing and developing formative evaluations, revising learning programs, designing and developing summative evaluations. This research involves learning, material, and media experts to measure media feasibility. Instruments and data collection techniques used in this research are questionnaires, interviews, observations, documentation, pre-test and post-test. This study adopted T-test analysis to analyze the effectiveness of the media developed based on pre-test and post-test data. This study produced Arabic learning media based on smart apps creator for class VIII MTs students, with a very feasible media quality category in the percentage of 93% by material experts, 96.25% by media experts, 93.3% by learning experts. Student responses to Arabic learning media based on smart apps creator are in the very interested category, with a percentage of 86% in small groups and 92% in large groups. Arabic learning media based on Smart Apps Creator is effective in learning. Arabic learning media based on Smart Apps Creator is effective in learning Arabic, with the difference in learning outcomes increasing to 38.75 with the results of the T-test analysis t0 = 62.5> ttabel = 2.093. Based on these findings, it can be said that the Arabic language learning media based on smart apps creator developed is classified as very feasible and very effective for learning Arabic.